1972
DOI: 10.1111/j.1751-1097.1972.tb06315.x
|View full text |Cite
|
Sign up to set email alerts
|

THE PHOTOCHEMICAL REACTIONS OF 1,3–DIMETHYLURACIL WITH 1–AMINOPROPANE AND POLY‐l‐LYSINE*

Abstract: Abstract— Irradiation of 1,3–dimethyluracil (DMU) in 1–aminopropane (AP) with u.v. light resulted in the formation of reduced and dimeric forms of DMU and adducts between DMU and AP. The formation of these compounds may be rationalized from the activation of either DMU or AP. Irradiation of DMU and poly‐l‐lysine in water with u.v. light resulted in the extensive binding of DMU to poly‐l‐lysine. The pyrimidine is probably attached to the ε‐carbon of the polypeptide at the 6–position. The biological implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1976
1976
1980
1980

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…It is possible that photoinduced reactions of uracil toward hydrocarbonlike side chains of amino acids will involve addition at both the 5 and 6 positions of the uracil ring. Reactivity at both of these positions has also been observed in the photoreactions of 1,3-DMU with I-aminopropane (Gorelic et al, 1972).…”
Section: Photoreactions Of Nucleic Acid Bases and Related Compounds Withmentioning
confidence: 79%
See 4 more Smart Citations
“…It is possible that photoinduced reactions of uracil toward hydrocarbonlike side chains of amino acids will involve addition at both the 5 and 6 positions of the uracil ring. Reactivity at both of these positions has also been observed in the photoreactions of 1,3-DMU with I-aminopropane (Gorelic et al, 1972).…”
Section: Photoreactions Of Nucleic Acid Bases and Related Compounds Withmentioning
confidence: 79%
“…Sato et al (1971) found that the irradiation of uracil, thymine and their analogs in formic acid led to the production of the corresponding dihydro derivatives. Gorelic et al (1972) discovered that DMU was photohydrogenated in the presence of l-aminopropane, while Shetlar (1975c) found that DMT was photo hydrogenated by 2-aminopropane. It was shown by Reeve and Hopkins (1975) that thymine and uracil, irradiated in the presence of tryptophan at A > 300 nm, were hydrogenated.…”
Section: Photochemical Hydrogenation Of Nucleic Acid Basesmentioning
confidence: 97%
See 3 more Smart Citations